Enhancing Early Childhood Learning through Interactive and Creative Approaches at RA Nurul Yaqin - Linda Afiyani; Jannati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to enhance the quality of early childhood education at RA Nurul Yaqin through the application of interactive and creative learning approaches. The study focuses on improving student engagement, motivation, and overall understanding by implementing innovative teaching methods that cater to the diverse learning needs of young children. The research is conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. Data is collected through classroom observations, student assessments, and feedback from teachers and parents. The results indicate that the interactive and creative learning approaches significantly improve children’s participation and enthusiasm in the learning process. By incorporating hands-on activities, storytelling, role-playing, and visual aids, students become more involved in lessons, making learning more meaningful and enjoyable. These activities also support the development of essential skills such as communication, social interaction, and problem-solving, which are crucial for early childhood growth. Furthermore, the research highlights the positive impact of these methods on the classroom environment. Students are more engaged, and their attention span improves during lessons. Teachers also report a greater sense of fulfillment and effectiveness in their teaching, as they observe the increased involvement of students. The application of these approaches fosters a supportive and nurturing learning atmosphere, where children feel encouraged to explore, ask questions, and express themselves. This study suggests that integrating interactive and creative learning strategies in early childhood education can lead to better learning outcomes and a more dynamic educational environment. It provides valuable insights for educators looking to enhance early childhood teaching practices and adapt to the diverse needs of young learners.